2009
DOI: 10.1038/cdd.2009.66
|View full text |Cite
|
Sign up to set email alerts
|

A new p63-deficient mouse model or a fresh look at an old one?

Abstract: The p53-related transcription factor p63 gene encodes six isoforms by the use of two promoters -TA and DN -and alternative splicing at the 3 0 -terminus, resulting in a, b, and g variants. Its critical importance in development has been illustrated by the discovery that dominantly inherited mutations in the p63 gene are found in a number of human ectodermal dysplasias with defects in limb and skin development, 1 and by the generation of mouse models lacking p63 by two independent laboratories. Although the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Based on further studies in embryos, the authors proposed these patches to be remnants of a more developed E15 epidermis 3–5 layers thick containing terminally differentiated epithelium that was transient in nature due to mechanical stress at birth, and suggested that the Brdm2 mice were equivalent to p63 α / β knockout mice [29]. This observation and ensuing studies generated much controversy, as to whether the recharacterized mice were the same as those used by others or if perhaps a spontaneous genetic event might be at play [2933], which to date remains unresolved.…”
Section: P63 and Normal Skin Biologymentioning
confidence: 99%
“…Based on further studies in embryos, the authors proposed these patches to be remnants of a more developed E15 epidermis 3–5 layers thick containing terminally differentiated epithelium that was transient in nature due to mechanical stress at birth, and suggested that the Brdm2 mice were equivalent to p63 α / β knockout mice [29]. This observation and ensuing studies generated much controversy, as to whether the recharacterized mice were the same as those used by others or if perhaps a spontaneous genetic event might be at play [2933], which to date remains unresolved.…”
Section: P63 and Normal Skin Biologymentioning
confidence: 99%
“…3). In addition to reversion events, other types of novel genetic changes could have occurred in the p63 Brdm2/Brdm2 mice, which may account for the phenotypic differences that were observed by Wolff et al (Reviewed by Aberdam and Mantovani (20)).…”
mentioning
confidence: 99%
“…25 It has an antiproliferative role, fundamental for skin development and differentiation, targeting the 3′-UTR of the transcription factor p63. 22, 26 Indeed, p63, a member of the p53 family, has an important role in maintaining basal keratinocyte proliferative potential in adult normal epidermis, 27, 28, 29, 30, 31, 32, 33 during development 34, 35, 36, 37 and in pathological conditions. 23, 24, 38, 39 MiR-203 downregulation, as described in several cancers, 42, 43, 44, 45, 46 promotes EMT transition and enables tumor cells to acquire invasive metastatic features.…”
mentioning
confidence: 99%